The Grande Riforma of the Italian constitution: majoritarian versus participatory democracy?. Issue 2 (4th May 2017) - Blokker, Paul
ABSTRACT: The economic crisis has triggered various constitutional reform processes in Europe, indicating a trend towards innovative forms of civic participation. In Italy, major constitutional reform attempts have been made since 2013. The article critically discusses the Italian case from the perspective of the meaningful participation of civil society and the citizenry in constitutional reform. First, it discusses civic participation in constitutional politics in theoretical terms, and places Italian constitutional reform in a comparative, European perspective. Second, the current reform is placed in the historical context of an Italian 'season of constitutional reform'. Third, the recent constitutional reform attempts are examined closely, with an emphasis on the main 'constitutional entrepreneurs', the reform process, and types of civic engagement with the reform. Fourth, 'constitutional resistance' to the Grande Riforma is discussed. The article concludes that the recent, unsuccessful, reform attempt neatly fits a repertoire of constitutional instrumentalism and majoritarianism that has emerged in the last 25 years, driven by mainstream parties, and displaying relatively little attention to civic participation in reform, while facing robust resistance from civil society and opposition parties.